2018
DOI: 10.18632/oncotarget.24702
|View full text |Cite|
|
Sign up to set email alerts
|

A phase II trial of 1st-line modified-FOLFOXIRI plus bevacizumab treatment for metastatic colorectal cancer harboring RAS mutation: JACCRO CC-11

Abstract: FOLFOXIRI plus bevacizumab is considered a standard initial therapy for metastatic colorectal cancer (mCRC). However, few prospective trials have evaluated triplet therapy plus bevacizumab in patients with RAS mutant mCRC. Patients with an age of 20 to 75 years, and unresectable, measurable tumors harboring RAS mutation were given first-line treatment with bevacizumab (5 mg/kg on day 1) plus modified-FOLFOXIRI (irinotecan 150 mg/m2, oxaliplatin 85 mg/m2, levofolinate 200 mg/m2, and fluorouracil 2400 mg/m2 as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 16 publications
2
19
1
1
Order By: Relevance
“…The subgroup analysis of PFS from our study showed that FOLFOXIRI-bevacizumab was superior in all patient subgroups, with the exception of those with PI3K- mutated tumours (n=43) or right-sided tumours (n=93), thus confirming the benefit of intensified therapy across a range of prognostic factors among patients with ≥3 CTC/7.5 mL blood. These subgroups included patients with RAS -mutated tumours (HR 0.80; 95% CI 0.56 to 1.16), and are consistent with a recent meta-analysis 17 and phase II study 18 supporting the first-line use of FOLFOXIRI-bevacizumab in RAS -mutated tumours. A positive effect of FOLFOXIRI-bevacizumab was also evident in patients with BRAF mutations (HR 0.83; 95% CI 0.37 to 1.86), although the effect size for this subgroup was smaller than reported in the TRIBE study (HR=0.55).…”
Section: Discussionsupporting
confidence: 85%
“…The subgroup analysis of PFS from our study showed that FOLFOXIRI-bevacizumab was superior in all patient subgroups, with the exception of those with PI3K- mutated tumours (n=43) or right-sided tumours (n=93), thus confirming the benefit of intensified therapy across a range of prognostic factors among patients with ≥3 CTC/7.5 mL blood. These subgroups included patients with RAS -mutated tumours (HR 0.80; 95% CI 0.56 to 1.16), and are consistent with a recent meta-analysis 17 and phase II study 18 supporting the first-line use of FOLFOXIRI-bevacizumab in RAS -mutated tumours. A positive effect of FOLFOXIRI-bevacizumab was also evident in patients with BRAF mutations (HR 0.83; 95% CI 0.37 to 1.86), although the effect size for this subgroup was smaller than reported in the TRIBE study (HR=0.55).…”
Section: Discussionsupporting
confidence: 85%
“…2) [3, 35], but has limitations. Specifically, RAS mutations may be associated with lesser benefit from chemotherapy plus bevacizumab compared with RAS wild type (WT) mCRC [3638], although the recent JACCRO CC-11 trial suggests that first-line mFOLFOXIRI (leucovorin, 5-FU, oxaliplatin, irinotecan) plus bevacizumab is effective for patients with RAS -mutated mCRC [39]. Treatment with aflibercept or ramucirumab (in combination with FOLFIRI) may be efficacious as second-line therapies for patients with RAS -mutated mCRC [3, 40].…”
Section: Biomarkers and Anti-egfr Therapy In Mcrcmentioning
confidence: 99%
“…Regarding the use of modified FOLFOXIRI therapy, there was no difference in toxicity between non-homozygous and homozygous polymorphisms. Thus, modified FOLFOXIRI therapy can be possibly performed safely [4].…”
Section: Discussionmentioning
confidence: 99%
“…The FOLFOXIRI therapy has a promising antitumor activity. However, due to its toxic side effects, several clinical trials were conducted for dose optimization [4]. In addition, there are antibodies approved for mCRC treatment, the anti-vascular endothelial growth factor (VEGF) antibodies (bevacizumab, ramucirumab, aflibercept) and the anti-epidermal growth factor receptor (EGFR) antibodies (cetuximab, panitumumab) used in mCRC with wild-type RAS gene.…”
Section: Introductionmentioning
confidence: 99%